MORPHOMETRIC MEASUREMENTS OF THE SKULL OF THE CROSS BRED CATTLE OF TIRUNELVELI DISTRICT WITH REFERENCE TO ANATOMICAL LANDMARKS - S. Rajathi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The aim of the study was to study the morphometrical measurements of the head region of adult Cross bred cattle without any apparent skeletal disorders and their clinical value for regional anaesthesia. 10 Cross Bred cattle were used and a total of 15 measurements were taken in the upper jaw and mandibles. The distance from the base of the horn to the caudal border of orbit, to mid level of dorsal arch of orbit and to rostral border of the orbit were 9.5 ± 0.22 cm, 11.5 ± 0.35 cm and 17.8 ± 0.56 cm respectively. The distance from the facial tuberosities to the infra-orbital canal and from the latter to the root of the alveolar tooth were 4.5 ± 0.06 cm and 4.0 ± 0.87 cm, respectively. The length and height of the mandible were 34.2 ± 0.72 cm and 21.0 ± 0.08 cm, respectively. The distance from the lateral alveolar root to the mental foramen and from the mental foramen to the caudal mandibular border were 4.5 ± 0.88 cm and 3.0 ± 0.32 cm, respectively. The distance from the mandibular foramen to the base of the mandible as well as from the caudal border of mandible to below of the mandibular foramen were 8.2 ± 0.11 cm and 4.5 ± 0.01 cm, respectively. The distance from the base of the mandible to the condyloid fossa and from the latter to the maximum height of the mandible were 16.2 ± 0.26 cm and 4.6 ± 0.25 cm, respectively. The distance from the caudal border of mandible to mandibular foramen and from the latter to the mandibular angle were 3.2 ± 0.97 cm and 6.6 ± 0.72 cm, respectively. These data were important landmarks with regard to the application to clinical procedure around the head of Cross bred cattle such as regional anaesthesia during dental extraction, dehorning and treating horn injury.